MKitchen training and development - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohd Ali, Noor Azian; Abdul Aziz, Normaziah; Mohamadali, Noor Azizah; Mahri, Nurhafizah; Ismail, Amelia Ritahani; et al. (Mkitchen, KICT IIUM Gombak, 2022)
This book provides mKitchen training and development. The training starts with preparation of mKitchen training materials. The training and development includes call for participation, selection, and induction processes prior to actual training activities. The first phase of training is process phase, which is team building to create ta’awun among team members with ta’aruf (get to know), tafahum (get to understand), takaful (get to protect) and tanashur (get to love and care) orientation. The second phase of training is content phase, which is the essential modules (social entrepreneurship, business model canvas, digital business and marketing, cash management, crowd funding, occupational safety, hygiene management, personality grooming, culinary art, cooking, distribution, and public engagement). One month has been allocated for both process and content phases of training. The final phase of the training is the internship. The minimum internship is within 12 weeks.